Interfacial deposition of Ag on Au seeds leading to AucoreAgshell in organic media - Chandran, S. Prathap; Ghatak, J.; Satyam, P. V.; Sastry, Murall (Journal of Colloid and Interface Science, 2007)
Keywords: core-shell nanoparticles; Gold; HRTEM; interfacial seeded growth; Silver; XPS

Short synthesis of (+)-harzialactone A and (R)-(+)-4-hexanolide via proline-catalyzed sequential alpha-aminooxylation and horner-wadsworth-emmons olefination of aldehydes - Kotkar, Shriram P.; Suryavanshi, Gurunath S.; Sudalai, Arumugarn (Tetrahedron-Asymmetry, 2007)
{In melts, ring polymers assume more compact conformations compared to linear chains with the same degree of polymerization N-r, i.e. R-r similar to N-r(nu) with nu approximate to 0.4, where R-r is the radius of gyration. Upon gradually substituting some of the ring polymers with linear chains, the ring molecules swell. In the limit of infinite dilution, their size scales as R-r similar to N-r(0.5). We present a scaling argument based on the blob model to capture this transition. Ring-linear blends are modeled as a semidilute solution of ring polymers in a theta-solvent consisting of linear chains. The model predicts that the size of the ring polymer remains unchanged up to the overlap concentration c(r)(*
Keywords: core-shell nanoparticles; Gold; HRTEM; interfacial seeded growth; Silver; XPS

Extracellular synthesis of crystalline silver nanoparticles and molecular evidence of silver resistance from morganella sp.: towards understanding biochemical synthesis mechanism - Parikh, Rasesh Y.; Singh, Sanjay; Bhagavatula L. V. Prasad; Patole, Milind S.; Sastry, Murali; Shouche, Yogesh S. (ChemBioChem, 2008)
There has been significant progress in the biological synthesis of nanomaterials. However, the molecular mechanism of synthesis of such bio-nanomaterials remains largely unknown. Here, we report the extracellular synthesis of crystalline silver nanoparticles (AgNPs) by using Morganella sp., and show molecular evidence I of silver resistance by elucidating the synthesis mechanism. The AgNPs were 20 +/- 5 nm in diameter and were highly stable at 1 room temperature. The kinetics of AgNPs formation was investigated. Detectable particles were formed after on hour of reaction, and their production remained exponential up to 18 h, and saturated at 24 h. Morganella sp. was found to be highly resistant to silver cations and was able to grow in the presence of more than 0.5 mm AgNO3. Three gene homologues viz. silE, silP and silS were identified in silver-resistant Morganella sp. The homologue of silE from Morganella sp. showed 99% nucleotide sequence similarity with the previously reported gene, silE, which encodes a periplasmic silver-binding protein. The homologues of silP and silS were also highly similar to previously reported sequences. Similar activity was totally absent in closely related Escherichia coli; this suggests that a unique mechanism of extracellular AgNPs synthesis is associated with silver-resistant Morganella sp. The molecular mechanism of silver resistance and its gene products might have a key role to play in the overall synthesis process of AgNPs by Morganella sp. An understanding of such biochemical mechanisms at the molecular level might help in developing an ecologically friendly and cost-effective protocol for microbial AgNPs synthesis.
Keywords: Biosynthesis; Morganella sp.; Nanoparticles; sil gene homologues; Silver

XPS and AFM investigations on silver-based photoimageable thick film systems - Umarji, Govind; Ketkar, Supriya; Hawaldar, Ranjit R.; Gosavi, Suresh W.; Patil, Kashinath; Mulik, Uttam P.; Amalnerkar, Dinesh P. (Microelectronics International, 2008)
Purpose - The purpose of this paper is to ascertain chemical changes occurring at various stages involved in processing of silver-based photoimageable thick films; and to determine ensuing topographical features which other wise appeared to be hindered in 2D scanning electron microscopy. Design/methodology/approach - Surface sensitive techniques, viz. X-ray photoelectron spectroscopy (XPS) and atomic force microscopy (AFM) were used. Findings - Interfacial adhesion of silver film with substrate (Al(2)O(3)) was specifically looked into with respect to role played by photoimaging (before and after exposure to ultra-violet light). XPS results revealed occurrence of subtle chemical changes in terms of unsaturation to saturation in C-C bonding and also an interesting C-Al bonding which presumably improves mechanical adhesion of unfired film with the alumina substrate. AFM was carried out to examine the surface roughness, particle size, and microstructure of film which are very important from the standpoint of high-frequency applications. Originality/value - Surface sensitive techniques like XPS and AFM were exclusively used in order to characterize silver-based photoimageable thick films.
Keywords: microscopy; Silver; thick film circuits; X-rays

Enhanced solar-radiation induced photocatalytic activity of surface-modified nanocrystalline anatase-titania - Priya, R.; Baiju, K. V.; Shukla, S.; Biju, S.; Reddy, M. L. P.; Patil, K. R.; Warrier, K. G. K. (Catalysis Letters, 2009)
Sol-gel derived pure nanocrystalline (similar to 20-30 nm) anatase-titania has been surface-modified by depositing silver(I) oxide and silver (predominantly the former) via UV-reduction process. The pure and surface-modified nanocrystalline anatase-titania have been characterized using different analytical techniques for determining the average nanocrystallite size, phase-contents, surface-chemistry, as well as the absorption and photoluminescence characteristics. It is demonstrated that, the latter exhibits an enhanced solar-radiation induced photocatalytic activity as compared to that of the former as a result of the absorption in the visible-region and enhanced photo-induced e(-)/h(+) life-time, both caused by the surface-deposition of silver(I) oxide and silver.
Keywords: Nanocrystalline; Photocatalysis; Silver; sol-gel; titania; UV-reduction

Silver fused conducting fiber formation of Au-Ag core-shell nanoparticles mediated by ascorbic acid - Murugadoss, A.; Kar, Manoranjan; Pasricha, Renu; Chattopadhyay, Arun (Plasmonics, 2009)
In this paper, we report the spontaneous formation of fibrous structures consisting of assemblies of Au-Ag core-shell nanoparticles (NPs) from a solution consisting of Au-Ag core-shell NPs and l-ascorbic acid (AA). AA acted both as the reducing agent for the generation of NPs and also as the mediator for the formation of fibers. The process of fiber formation involved three steps-reduction of HAuCl(4) to Au NPs by AA, subsequent formation of Au-Ag core-shell NPs after addition of AgNO(3), and spontaneous formation of fibers from the mixtures in water. It took typically about 30 days to form complete fibers that are of lengths of several hundred micrometers to millimeters, although nanofibers started forming from the first day of solution preparation. The width of each of these fibers was typically about 1-4 A mu m with length of each segment of fiber bundle, on the order of 40 A mu m. Formation of fibers was also observed in absence of AgNO(3). These fibers consisted of Au NPs and polymer of AA degradation products and were not electrically conducting. Also, low concentrations of AgNO(3) produced fibers with low electrical conductivity. However, it was observed that increase in the amount of AgNO(3) leads to the formation of fibers that were electrically conducting with conductivity values in the range of metallic conductivity. Spectroscopic and electron microscopic investigations were carried out to establish the formation of fibers. The details of fiber formation mechanism under different conditions and electrical conductivities of the fibers are discussed in the article.
Keywords: Ascorbic acid; core-shell; Fiber; Gold; Nanoparticles; Silver

Morphological changes in nanoparticulate silver films due to electron beam irradiation of polystyrene substrates - Pattabi, Manjunatha; Gurumurthy, S. C.; Sanjeev, Ganesh; Gaikwad, A. B. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions With Materials and Atoms, 2011)
Results of the studies on the effect of 8 MeV electron beam irradiation of polystyrene substrates on the morphology of silver particulate films deposited at 455 K in a vacuum of 8 x 10(-6) Torr are reported. Optical absorption studies show the presence of transverse and longitudinal plasmon resonance for films deposited on irradiated polystyrene. Scanning electron microscopy reveals a decrease in particle size with smaller inter-particle separation for irradiated films. Larger clusters are formed in the case of films deposited on polystyrene after 300 h of irradiation. In this paper, we show that the morphology of silver nanoparticulate films can be modified by electron irradiation of inert polymer substrates like polystyrene. The change observed due to irradiation is attributed to the formation of free radicals, thereby altering the polymer-metal interaction. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Electron bombardment; Optical properties; Particulate films; Polymers; Silver; surface morphology

Green approach towards size controlled synthesis of biocompatible antibacterial metal nanoparticles in aqueous phase using lysozyme - Kumar, Umesh; Ranjan, Amaresh K.; Sharan, Chandrashekhar; Hardikar, Anandwardhan A.; Pundle, Archana; Poddar, Pankaj (Current Nanoscience, 2012)
Inspired by array of proteins present in nature, we choose lysozyme (hen egg protein) as a model system to synthesize nanoparticles of noble metals to understand the mechanism of interaction as well as to use them for potential applications such as potent antibacterial agents. Lysozyme is a very well studied biomolecule containing aromatic amino acids like tryptophan and tyrosine. Tyrosine has phenoxy group which is considered to be responsible for interacting with the metal ions. Lysozyme can be suitably modified by treatment with N-bromosuccinimide/N-acetylimidazole to obtain tight control over size distribution of nanoparticles. Here we report the direct synthesis of nanocrystals of gold and silver at controlled pH and light conditions without using any known reducing agents. Out of these, synthesis of gold nanoparticles is assisted by the presence of low concentration of Ag+ ions through the galvanic exchange. It is remarkable to note that the structure of protein is not changed drastically as seen by the FTIR studies. As-synthesized lysozyme capped nanoparticles prepared by this method are biocompatible and retain antibacterial property.
Keywords: Antibacterial; Biocompatible; Gold; lysozyme; Nanoparticles; Silver

Biological synthesis of silver nanoparticles using the fungus humicola sp and evaluation of their cytoxicity using normal and cancer cell lines - Syed, Asad; Saraswati, Supriya; Kundu, Gopal C.; Ahmad, Absar (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2013)
Nanoscience is a new born science of the modern era and taps into the potential of particles at nanoscale. Bulk materials reduced to nanoscale dimensions thus obtain unique properties such as electronic, optical, magnetic and chemical. As far as synthesis of nanoparticles is concerned, biological synthesis has recently sparked a great interest as compared to other available chemical and physical methods on account of its eco-friendliness and cost-effectiveness. Here we report, for the first time, the biosynthesis of silver nanoparticles by the thermophilic fungus Humicola sp. The fungus when reacted with Ag+ ions reduces the precursor solution and leads to the formation of extracellular nanoparticles as monitored by ultra violet visible spectroscopy (UV-Vis). The morphology of nanoparticles is found to be spherical with good dispersity as revealed by transmission electron microscopy (TEM). Cell viability assays were carried out to assess the cytotoxicity of silver nanoparticles on NIH3T3 mouse embryonic fibroblast cell line and MDA-MB-231 human breast carcinoma cell line. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Cell viability; Fungus; Humicola sp.; Nanoparticles; Silver

Extracellular synthesis of silver nanoparticles using living peanut seedling - Raju, D.; Paneliya, Nikita; Mehta, Urmil J. (Applied Nanoscience, 2014)
Synthesis of nanoparticles by environment friendly method is an important aspect of nanotechnology. In the present study, extracellular reduction of silver ions to silver nanoparticles was carried out using living peanut plant. The electron microscopic analysis shows that the formed nanoparticles were of different shapes and sizes. The formed nanoparticles were polydispersed. The shapes of the nanoparticles were spherical, square, triangle, hexagonal and rod. Most of the particles were spherical and 56 nm in size. EDS analysis confirmed the formed nanoparticles were of silver. The crystalline nature of nanoparticles was confirmed by diffraction. This method opens up an exciting possibility of plant-based synthesis of other inorganic nanomaterials. This study confirms the synthesis of extracellular silver nanoparticles by living plant.
Keywords: Nanoparticles; Shapes; Silver; synthesis; TEM

Protein mediated synthesis of Au-Ag bimetallic nanoparticles - Raju, D.; Mendapara, Ritul; Mehta, Urmil J. (Materials Letters, 2014)
There is growing need to develop environment friendly method for synthesis of bimetallic nanoparticle that do not use toxic chemicals during their synthesis process. Here, we report synthesis of Au-Ag bimetallic nanoparticles by using macerase enzyme as reducing agent at different temperatures. Bimetallic nanoparticles were synthesized at 80 and 90 degrees C. The intensity of formation of nanoparticles was more at 80 degrees C. The bimetallic nanoparticles are characterized by using UV-vis, TEM and EDAX. The TEM study shows the inner gold and outer silver bimetallic nanoparticles. The formed nanoparticles are 4-20 nm in size and spherical in shape. EDAX confirms the formed bimetallic nanoparticles are of gold and silver. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Enzyme; Gold; Macerase; Particles; Silver; synthesis

Electronically integrated mesoporous Ag-TiO2 nanocomposite thin films for efficient solar hydrogen production in direct sunlight - Mani, Sunesh S.; Rajendran, Sivaraj; Nalajala, Naresh; Mathew, Thomas; Gopinath, Chinnakonda S. (Energy Technology, 2021)
The synthesis of mesoporous TiO2 by a solution-based assembly process and Ag/TiO2 nanocomposites is provided. The efficacy of Ag/TiO2 nanocomposite as photocatalyst in thin-film form is demonstrated for solar hydrogen generation in sunlight. Integration of Ag with TiO2 dramatically enhanced the H-2 production: with 1 wt% Ag on TiO2 (TiAg-1), the H-2 yield was observed to be 4.59 mmol h(-1) g(-1), which is 2.3 (30) times larger than 0.5 wt% Ag on TiO2. TiAg-1 shows 4.3 times higher activity in film form compared with its powder counterpart. High photocatalytic efficiency is attributed to the surface plasmon resonance effect of Ag, electronic integration of Ag with TiO2, and subsequent valence band broadening, large distribution of Ag nanoparticles and abundant Ag-TiO2 Schottky junctions, and the later minimizes electron-hole recombination. Interparticle mesoporous network increases necking and the high surface area offers easy accessibility of the reactants to a large number of active sites.
Keywords: heterogeneous catalysis; heterojunctions; plasmon effect; Silver; solar energy conversion; Solar hydrogen

Methanol-to-light olefins reaction using Zn-Ag modified SSZ-13 catalyst - Dange, Rutvija M.; Gawali, Chirag B.; Niphadkar, Prashant S.; Bokade, Vijay V.; Nandanwar, Sachin U. (ChemistrySelect, 2022)
The 2 wt.% of Zn and Ag (Zn1-x-Ag-x; x=0.2, 0.4, 0.6 %) modified SSZ-13 (SZ-13) zeolite was prepared by wet-impregnation method, and its catalytic activity was demonstrated for methanol-to-olefin (MTO). The Zn-0.6-Ag-0.4/SZ-13 catalyst exhibited high catalytic activity due to change in properties of catalyst. The Zn particles were highly dispersed inside the SZ-13; while Ag particles were dispersed on the surface of SZ-13, confirmed by HRTEM and surface area. The small % of Ag over SZ-13 promotes ethylene production via aromatization of reaction, and highly dispersed Zn on SZ-13 help to produce stable ethylene and propylene. The Zn-0.6-Ag-0.4/SZ-13 catalyst showed (similar to 10 %) higher light olefin (87 %) selectivity than parent SZ-13 as well as mono metal incorporated SZ-13. The higher catalytic activity was attributed due to effect of both metals (Zn and Ag), where Ag promotes partial aromatization on the surface, and Zn increases the Lewis acidity in the zeolite pore. This catalyst can help to improve the selectivity of light olefin using MTO reaction.
Keywords: Ethylene; Methanol-to-Olef; Propyl; Silver; SSZ; zinc

Silver dependent enantiodivergent gold(i) catalysed asymmetric intramolecular hydroamination of alkenes: a theoretical study - Dixit, Ruchi; Sharma, Himanshu; Agbossou-Niedercorn, Francine; Vanka, Kumar; Michon, Christophe (Catalysts, 2022)
We report a theoretical study of the first silver-dependent enantiodivergent gold-catalysed reaction. The combination of a single chiral binuclear gold(I) chloride complex and silver perchlorate catalyses the asymmetric intramolecular hydroamination of alkenes and affords both enantiomers of the products by applying a simple solvent change from toluene to methanol. A gold-silver chloride adduct that occurs only in methanol appears to control the enantioinversion. If one gold atom coordinates and activates the alkene moiety, the other gold is included in an adduct with silver chloride, which coordinates a methanol solvent molecule and further interacts with the amine function. If the use of toluene implies free anions and affords (S)-enantiomer, methanol allows a proximal interaction with the amine, leads to an opposite stereodifferentiation of the two diastereomeric intermediates during the final protodeauration step and results in the (R)-enantiomer.
Keywords: alkene; enantiodivergent catalysis; Gold; hydroamination; Silver